Epidemiological investigation of infectious occupational exposure among dental students in a stomatological teaching hospital: a cross-sectional study - Tang, Na; He, Si; Li, Sha (Frontiers in Public Health, 2025)
PurposeTo analyze the infectious occupational exposure status and related factors in stomatological hospital students.MethodsThe infectious occupational exposure data reported by students in Changsha Stomatological Hospital from 2019 to 2023 were collected and analyzed from three aspects: basic situation, exposure situation and emergency treatment after exposure.ResultsA total of 1,151 students were investigated from 2019 to 2023, and 48 of them had infectious occupational exposure, with an occupational exposure rate of 4.17%. Interns (6.44%) had the highest rate of occupational exposure to infectious diseases, and most of the exposures were related to handling medical waste (62.50%) and puncture wounds by hollow needles (70.83%). Maxillofacial surgery (54.17%) was the department with the highest proportion of students with infectious occupational exposure. The investigation showed that although none of the exposed students were infected after follow-up, 56.25% of the students still did not receive proper emergency treatment after infectious occupational exposure, and 16.67% of the students did not receive timely report after exposure.ConclusionDental students have a high risk of occupational exposure to infectious diseases, so it is very important to strengthen their occupational protection awareness and operational skills, standardize the emergency treatment measures and reporting procedures of students after occupational exposure, and ensure the correct treatment and reporting of dental students after occupational exposure.